Peran Konservasi Sumber Daya Alam Terhadap Pelestarian Lingkungan di Desa Wisata Benowo Park - Salsabilla Syifa Azzahra; Sanita Carolina Sasea (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study aims to analyze the role of socio-cultural conservation in maintaining environmental sustainability and the role of tourism managers in increasing tourists' awareness of ecosystem preservation in ecotourism in Benowo Park, Pemalang Regency. The background of this study is the high threat of ecosystem damage in the tourism environment, especially in the era of exploitative modernization. This study uses a descriptive qualitative approach with data collection techniques namely through observation, interviews, and documentation. The research findings indicate that local wisdom has strategic potential in maintaining environmental sustainability, especially through the community's social system that regulates norms, compliance, and boundaries in interacting with nature. Area managers and local champions play a crucial role in integrating traditional values with modern tourism operations to maintain relevance. This integration includes "Klitik Wood Coin" transactions, restrictions on plastic packaging, preservation of the Mbah Benowo, facilitation of digital literacy, and collaboration on Javanese song art education. The implementation of this conservation has resulted in changes in tourist behavior from an exploitative lifestyle to one that is more obedient, respectful, and aware of the limits of interaction with nature and how to preserve it.